Case report: A reciprocal translocation-free and pathogenic DUOX2 mutation-free embryo selected by complicated preimplantation genetic testing resulted in a healthy live birth - Shi, Biwei; Ye, Yinghui (Frontiers in Genetics, 2023)
Preimplantation genetic testing (PGT) is an effective approach to improve clinical outcomes and prevent transmission of genetic imbalances by selecting embryos free of disease-causing genes and chromosome abnormalities. In this study, PGT was performed for a challenging case in which a couple simultaneously carried a maternal subchromosomal reciprocal translocation (RecT) revealed by fluorescence in situ hybridization involving the chromosome X (ChrX) and heterozygous mutations in dual oxidase 2 (DUOX2). Carriers of RecT are at increased risk for infertility, recurrent miscarriages, or having affected children due to the unbalanced gametes produced. DUOX2 mutation results in congenital hypothyroidism. Pedigree haplotypes for DUOX2 was constructed after the mutations were verified by Sanger sequencing. Since male carriers of X-autosome translocations may exhibit infertility or other abnormalities, pedigree haplotype for chromosomal translocation was also constructed to identify embryo with RecT. Three blastocysts were obtained by in vitro fertilization and underwent trophectoderm biopsy, whole genomic amplification, and next-generation sequencing (NGS). A blastocyst lacking copy number variants and RecT but carrying the paternal gene mutation in DUOX2, c.2654G>T (p.R885L) was used for embryo transfer, resulting in a healthy female infant whose genetic properties were confirmed by amniocentesis. Cases containing RecT and single gene disorder are rare. And the situation is more complicated when the subchromosomal RecT involving ChrX cannot be identified with routine karyotype analysis. This case report contributes significantly to the literature and the results have shown that the NGS-based PGT strategy may be broadly useful for complex pedigrees.